Qualidade do leite UAT sob diferentes condições de armazenamento - Amanda Ribeiro dos Santos (2019)
UHT milk is the most consumed fluid milk by the Brazilian population, because of the easy storage at room temperature. However, such storage, when prolonged, may result in loss of quality, integrity and safety, mainly due to the action of thermoresistant enzymes that remain active after processing. Although the Brazilian Regulation of UHT milk establishes requirements for fat content, acidity, ethanol stability and the counting of aerobic mesophilic microorganisms. It is observed that only these parameters may not be adequate to verify the quality of this milk. The objective of this study was to evaluate the physicochemical and microbiological changes that occur during UHT milk storage for up to 120 days. A total of 120 UHT milk samples were collected from two dairy industries in the state of Minas Gerais, stored at two temperatures (20°C/ 30°C) and five periods (0, 30, 60, 90, and 120 days). A completely randomized design was used in a 2x2x5 factorial arrangement, with a total of 20 treatments, with six replicates per treatment (six batches). The objective of this study was to evaluate: aerobic mesophilic microorganisms counting, centesimal composition, somatic cell count, acidity, density, freezing point, lipolysis index and caseinomacropeptide (CMP), as well as the residues of preservatives and other illegal substances added to UHT milk. When compared to the Brazilian parameters for UHT milk, the average values of acidity, fat and solids non-fat (SNF) contents remained within the acceptable values until the last day of storage. However, the other parameters [density, freezing point, lipolysis index, somatic cell count (SCC), lactose, total solids (TS), casein and protein content, and CMP] are not covered by specific legislation of UHT milk in Brazil. Density, SCC, aerobic mesophilic microorganisms and Total Bacterial Count (TBC) did not change due to storage time and temperatures, and industries. There was a gradual and significant increase (p < 0.05) only at day 120. The different temperatures and industries resulted in considerable changes of freezing point, lactose, TS and SNF contents and CMP, showing that low milk quality and increasing storage temperatures may intensify the changes that occur in milk. No extraneous substances, such as neutralizers of the acidity, density modifiers, preservatives or residues of antibiotics were detected. The results show that there is a gradual loss of UHT milk quality during its shelf life, which is related to the raw milk quality and storage time. In addition, UHT milk legislation could be improved with the addition of new quality control parameters to improve quality monitoring during storage, such as CMP index.